Design and characterisation of magnetorheological brake system. (4th December 2014) - Zainordin, Ahmad Zaifazlin bin; Hudha, Khisbullah; Jamaluddin, Hishamuddin; Nuri, Nur Rashid bin Mat
This paper investigates the performance of a magnetorheological brake (MR brake) system in terms of torque generated by various electric currents at various rotational shaft speeds. The MR brake consists of a rotating disc immersed with magnetorheological fluid (MR fluid) in an enclosure of an electromagnetic coil. The applied magnetic field will increase the yield strength of the MR fluid, which will decrease the speed of the rotating shaft. Then, different speeds were applied to the MR brake system continuously by changing the applied electric current. The methodology begins with the design using 3D modelling software followed by the development of a mathematical model of the MR brake. Then, magnetostatic analysis using ANSYS software was done by considering three parameters, which are magnetic field intensity, magnetic flux density and 2D flux lines. The torque response of the MR brake from the simulation was validated with experimental results and discussed. It can be noted that the MR brake torque increases proportionally with the increase in current and independent with varying speeds.